Reer Review: Adjusment to Target Capital Structure oflndonesia Firms:Dynamic Capital Structure Model. Intenational Infrastructure Conference 2014, - Dr. Arni Surwanti, M.Si. (International Infrastructure Conference 2014, 2014)
International Infrastructure Conference 2014 Desember 2014 Inliasftucture University Kuala Lumpur Target Capital Structure lndonesia Firms: Dynamic Capital Structure Model. Intenational Infrastructure Conference 2014,